2023
DOI: 10.1038/s41598-023-27595-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimum processing conditions for the maximum crystallization rate of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)

Abstract: The effect of thermal and shear histories on the crystallization rate of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) was studied. As with other crystalline polymers, the shear history greatly affected the crystallization rate when the shear rate was beyond a critical value, i.e., the inverse of the Rouse relaxation time. Even after the formation of extended chain crystals, spherulite texture was clearly discernable. It grew from certain points on the extended chain crystals. Consequently, a row of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…Moreover, the alignment of shish to the flow direction led to the orientation of crystalline chains grown during annealing. Similar results were recently reported for isotactic polypropylene containing fibrous nucleating agents and polyhydroxyalcanoate [ 38 , 39 , 40 ], although the crystal growth did not occur during post-processing annealing in these studies. This anomalous growth of molecular orientation for PLA will be important for the dimensional control and mechanical properties, such as modulus and its anisotropy.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the alignment of shish to the flow direction led to the orientation of crystalline chains grown during annealing. Similar results were recently reported for isotactic polypropylene containing fibrous nucleating agents and polyhydroxyalcanoate [ 38 , 39 , 40 ], although the crystal growth did not occur during post-processing annealing in these studies. This anomalous growth of molecular orientation for PLA will be important for the dimensional control and mechanical properties, such as modulus and its anisotropy.…”
Section: Resultssupporting
confidence: 90%
“…The results obtained agree with the data of publications [81,98,99], which describe the regularities in the formation of spherulites during the isothermal crystallization of P(3HB-co-3HHx) copolymers. The authors of these works have shown that in P(3HB-co-3HHx) samples, the formation of banded spherulites similar to those obtained in this work, with a well-pronounced Maltese cross depending on the crystallization temperature of the melt, is possible.…”
Section: Effect Of 3-hydroxyhexanoate Monomers Incorporated Into the ...supporting
confidence: 88%
“…The kinetics of crystallization is an important consideration in polymer processing as it significantly affects the final thermal and mechanical properties of materials. The Avrami equation (Equation (5)) is the most widely used method for analyzing the crystallization kinetics of polymers [ 48 , 49 ]. However, the limitations of this model have been found; for example, it is only applicable to primary crystallization.…”
Section: Crystallization Principlesmentioning
confidence: 99%